Long‐Term Earth‐Moon Evolution With High‐Level Orbit and Ocean Tide Models - Daher, Houraa; Arbic, Brian K.; Williams, James G.; Ansong, Joseph K.; Boggs, Dale H.; Müller, Malte; Schindelegger, Michael; Austermann, Jacqueline; Cornuelle, Bruce D.; Crawford, Eliana B.; Fringer, Oliver B.; Lau, Harriet C. P.; et al. (Journal of geophysical research. Planets, 2021)
Tides and Earth‐Moon system evolution are coupled over geological time. Tidal energy dissipation on Earth slows Earth′s rotation rate, increases obliquity, lunar orbit semi‐major axis and eccentricity, and decreases lunar inclination. Tidal and core‐mantle boundary dissipation within the Moon decrease inclination, eccentricity and semi‐major axis. Here we integrate the Earth‐Moon system backwards for 4.5 Ga with orbital dynamics and explicit ocean tide models that are “high‐level” (i.e., not idealized). To account for uncertain plate tectonic histories, we employ Monte Carlo simulations, with tidal energy dissipation rates (normalized relative to astronomical forcing parameters) randomly selected from ocean tide simulations with modern ocean basin geometry and with 55, 116, and 252 Ma reconstructed basin paleogeometries. The normalized dissipation rates depend upon basin geometry and Earth′s rotation rate. Faster Earth rotation generally yields lower normalized dissipation rates. The Monte Carlo results provide a spread of possible early values for the Earth‐Moon system parameters. Of consequence for ocean circulation and climate, absolute (un‐normalized) ocean tidal energy dissipation rates on the early Earth may have exceeded today′s rate due to a closer Moon. Prior to ∼3 Ga, evolution of inclination and eccentricity is dominated by tidal and core‐mantle boundary dissipation within the Moon, which yield high lunar orbit inclinations in the early Earth‐Moon system. A drawback for our results is that the semi‐major axis does not collapse to near‐zero values at 4.5 Ga, as indicated by most lunar formation models. Additional processes, missing from our current efforts, are discussed as topics for future investigation. Plain Language Summary Tidal dissipation in Earth′s oceans and solid body cause the distance to the Moon and the length of day to increase over time. Tides also change the eccentricity and tilt of the lunar orbit, and Earth′s obliquity (the tilt between the equator plane and the ecliptic plane of our orbit around the Sun). This paper attempts to calculate the evolution of the Earth‐Moon system over the whole of Earth′s history using sophisticated ocean tide and orbit models. Over long time scales, the rate at which tidal energy is being dissipated is affected by the geometrical configuration of the continents, the length of day, and mean sea level, which is affected by plate tectonic forces and the presence or absence of large ice caps. The faster rotating Earth of the past was less efficient at dissipating energy and the present placement of the continents enhances some tides due to resonances. In addition, tidal dissipation in the Moon slows the orbit evolution by absorbing energy from the orbit and there was a time in the distant past when the Moon′s tidal dissipation was large. The evolution of the Earth‐Moon system is complex and uncertain, but it can be addressed with advanced models. Key Points Long‐term Earth‐Moon system evolution is estimated with backwards‐in‐time integrations using high‐level orbit and ocean tide models Rapid Earth rotation reduces paleotidal energy dissipation rate relative to paleotidal forcing. Ocean basin geometry is another key factor Tidal and core/mantle boundary dissipation within the Moon significantly impact the orbital evolution from about 3–4.5 Ga in the past